Effect of Feeding Moringa oleifera Meal on Growth Performance of Growing Surti Kids under Intensive System of Management - Pandey, Anushri; Modi, Rakesh J.; Lunagariya, Pravin M.; Islam, Manzarul (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A 14 weeks study was carried out on eighteen Surti kids of 6-8 months of age. The kids were randomly divided into three treatment  groups, with six in each group based on the same age and uniform conformation to evaluate the effect of Moringa oleifera meal (MOM)  on growth performance. After 15 days of the adaptation period, kids were offered total mixed ration (TMR) by replacing commercial  concentrate with MOM at 0, 25, and 50 % inclusion rates by maintaining a constant protein level in all the dietary rations. The results  showed that kids fed on three different inclusion rates of M. oleifera meal in concentrate did not reveal significant differences in their  overall body weight, total body weight gain, and biometry (body length and heart girth), except height at wither, which was significantly  (p
Keywords: Growth performance; M. oleifera meal (MOM); Surti kids